Combined biochar and DMPP reduce N2O emissions in wheat crops via microbial community modulation - Wu, Haizhong; Zhang, Dengxiao; Shen, Xiaobo; Ma, Guozhen; Yuan, Qingsong; Zhao, Hongjing; Liu, Shiliang; Jie, Xiaolei; Wang, Daichang (Frontiers in Plant Science, 2025)
Delayed nitrogen (N) application increases N use efficiency in a broadacre cropping system. However, its effect on N2O emissions and the underlying microbial mechanisms remains poorly understood. A field-plot experiment was carried out to examine the effects of biochar and a nitrification inhibitor (DMPP) on soil N2O emissions with six treatments: without N application (control), optimal N application (ON), farmer conventional N application (FN), biochar + ON (ONB), DMPP + ON (OND), and biochar + OND (ONDB). In comparison to the ON treatments, cumulative N2O emissions from the OND and ONDB treatments were significantly reduced by 32% and 38%, respectively, whereas emissions from the FN and ONB treatments exhibited increases of 38% and 4%, respectively. N application or biochar amendment increased the abundance of AOA and AOB, whereas DMPP amendment led to a reduction in AOB abundance. The OND and ONDB treatments enhanced the relative proportion of Nitrospira in the AOB community. The ONB treatment altered the most dominant genus of nirS and nosZ communities. Correlation analysis revealed that AOB, nirK, and nirK/nosZ were the predominant microorganism communities influencing soil N2O emissions. Random forest analysis identified Nitrospira in AOB communities, Cronobacter in nirK-containing communities, and Ramlibacter and Methylobacillus in the nosZ-containing community as key microbial taxa contributing to N2O emissions. We propose that the ONBD treatment provides dual advantages by reducing N2O emissions and enhancing N use efficiency under the delayed N application regime.